2015
DOI: 10.1161/circinterventions.115.002909
|View full text |Cite
|
Sign up to set email alerts
|

Demystifying Complex Coronary Hemodynamics in Patients Undergoing Transcatheter Aortic Valve Replacement

Abstract: T ranscatheter aortic valve replacement (TAVR) has revolutionized the treatment of patients with severe aortic stenosis who are at high risk for traditional surgical intervention.1,2 As the technology matures and experience grows, the applicability of TAVR to lower risk populations is likely and is already being explored. 3 These patients often present with chest pain or exertional dyspnoea in the context of varying degrees of coronary artery disease. An understanding of how the aortic valve affects coronary h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…Stenosis at the level of the aortic valve is anatomically below the coronary artery in ow resulting in reduced coronary perfusion pressure (23). Previous studies have shown greater CFR impairment with increasing severity of AS and LV remodelling (24).…”
Section: Myocardial Perfusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stenosis at the level of the aortic valve is anatomically below the coronary artery in ow resulting in reduced coronary perfusion pressure (23). Previous studies have shown greater CFR impairment with increasing severity of AS and LV remodelling (24).…”
Section: Myocardial Perfusionmentioning
confidence: 99%
“…Previous studies have shown greater CFR impairment with increasing severity of AS and LV remodelling (24). Relief of the stenosis therefore results in an acute reduction in the left ventricular end diastolic pressure (LVEDP) resulting in increased coronary perfusion (23). Furthermore, the augmentation in coronary ow is linearly related to aortic valve area and coronary perfusion pressure during stress/hyperaemia (6).…”
Section: Myocardial Perfusionmentioning
confidence: 99%
“…Scarsini and colleagues should be congratulated for attempting to define coronary stenosis severity physiologically in the context of aortic stenosis. Their study contributes to a growing number of studies that are beginning to unpick the complex physiology in these patients 14 . The ability to elucidate coronary stenosis severity independent of aortic valve severity may become increasingly clinically relevant as the use of TAVI increases and it is applied to a larger and lower-risk patient population 15,16 .…”
Section: The Importance Of Stenosis Distributionmentioning
confidence: 99%